Pathological Relevance of Anti-Hsp70 IgG Autoantibodies in Epidermolysis Bullosa Acquisita - Tukaj, Stefan; Mantej, Jagoda; Sitko, Krzysztof; Zillikens, Detlef; Ludwig, Ralf J.; Bieber, Katja; Kasperkiewicz, Michael (Frontiers in Immunology, 2022)
Stress-induced heat shock protein 70 (Hsp70) is a key intra- and extracellular molecular chaperone implicated in autoimmune processes. Highly immunogenic Hsp70 can activate the immune response driving the generation of anti-Hsp70 autoantibodies that are frequently found in autoimmune disorders. We recently described the direct pathological role of extracellular Hsp70 in epidermolysis bullosa acquisita (EBA), an anti-type VII collagen (COL7) autoantibody-mediated blistering dermatosis. Here, we determined the role of anti-Hsp70 autoantibodies in EBA. We observed that serum levels of anti-Hsp70 IgG autoantibodies were significantly elevated in EBA patients compared to healthy controls and positively correlated with serum levels of pro-inflammatory interferon gamma (IFN-). The pathophysiological relevance of anti-Hsp70 IgG autoantibodies was demonstrated in an anti-COL7 antibody transfer-induced EBA mouse model in which elevated blood levels of anti-Hsp70 IgG were recorded. In addition, anti-Hsp70 IgG-treated mice had a more intense clinical and histological disease severity, as well as upregulated nuclear factor kappa B (NF-κB) activation in skin biopsies compared to isotype-treated animals. Our results suggest that autoantibodies to Hsp70 may contribute to EBA development via enhanced neutrophil infiltration to the skin and activation of the NF-κB signaling pathway in an IFN--associated manner.